Using Pictures to Improve Students' Vocabulary in Fifth Grade of SD Negeri Wakarleli - Salmon, Nice Violeta; Hukom, Salmon James; Tiwery, Yulina (Koli Journal : English Language Education, 2024)
This study aims to improve student's vocabulary mastery in the fifth grade of SD Negeri Wakarleli using pictures as visual media. The research was conducted as Classroom Action Research (CAR) in two cycles involving 20 students. Both qualitative and quantitative data were collected using observation checklists and pre-tests/post-tests. The findings indicate a significant improvement in students' vocabulary acquisition through pictures, especially in fruits and occupations. The results show that in the second cycle, more students reached 'excellent' and 'very good' levels of vocabulary mastery compared to the first cycle. These results suggest that using pictures as teaching media improves vocabulary acquisition